Genome-Wide Association Study Implicates Testis-Sperm Specific FKBP6 as a Susceptibility Locus for Impaired Acrosome Reaction in Stallions - Raudsepp, Terje; McCue, Molly E.; Das, Pranab J.; Dobson, Lauren; Vishnoi, Monika; Fritz, Krista L.; Schaefer, Robert; Rendahl, Aaron K.; Derr, James N.; Love, Charles C.; Varner, Dickson D.; Chowdhary, Bhanu P. (PLOS Genetics, 2012)
Author Summary Impaired acrosomal reaction (IAR) of sperm causes male subfertility in humans and animals, and currently the molecular causes of the condition are not known. Here we report the mapping, identification, and functional analysis of a susceptibility locus for IAR in stallions. The candidate region was mapped to horse chromosome 13 by SNP genotyping and GWAS of 7 IAR affected and 44 control Thoroughbred stallions. Re-sequencing and case-control analysis of functionally relevant candidate genes in the region identified FKBP6 gene as a significantly associated locus. The association was confirmed by genotyping 265 male horses of multiple breeds. FKBP6 belongs to the immunophilins FKBP family known to be involved in meiosis, calcium homeostasis, clathrin-coated vesicles, and membrane fusions. We showed that the equine FKBP6 is exclusively and monoallelically expressed in testis and sperm and has 5 different transcripts, of which 4 were novel. Overall, FKBP6 was considered a susceptibility gene of incomplete penetrance for IAR in stallions and a candidate gene for male subfertility in other mammals. Successful use of sperm as a source of DNA and RNA propagates non-invasive sample procurement for fertility genomics in animals and humans.